2019
DOI: 10.1097/coc.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Differential Outcomes Among Immunosuppressed Patients With Merkel Cell Carcinoma

Abstract: Objectives: Merkel cell carcinoma (MCC) is a rare, aggressive neuroendocrine skin cancer with higher incidence among whites, elderly, and immunosuppressed patients. Although immunosuppressed MCC patients are at higher risk of recurrence and MCC-related death, it is unknown whether immunosuppression type is associated with differential outcomes. Materials and Methods: We retrospectively evaluated 89 nonmetastatic MCC patients with a diagnosis of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 35 publications
0
17
0
2
Order By: Relevance
“…This has been demonstrated in studies analyzing effect immunosuppression on Merkel cell cancer and cutaneous squamous cell cancer of head and neck. 108,109 In patients with cutaneous squamous cell carcinoma, immunosuppression was associated with worse 5-year disease-specific survival (68% versus 84%) and overall survival (37% versus 59%). 108 However, a considerable number of these patients had immunosuppression secondary to medical comorbidities, such as lymphoma or leukemia (27%) and HIV (2%), rather than immunosuppressive medications.…”
Section: Immunotherapymentioning
confidence: 99%
“…This has been demonstrated in studies analyzing effect immunosuppression on Merkel cell cancer and cutaneous squamous cell cancer of head and neck. 108,109 In patients with cutaneous squamous cell carcinoma, immunosuppression was associated with worse 5-year disease-specific survival (68% versus 84%) and overall survival (37% versus 59%). 108 However, a considerable number of these patients had immunosuppression secondary to medical comorbidities, such as lymphoma or leukemia (27%) and HIV (2%), rather than immunosuppressive medications.…”
Section: Immunotherapymentioning
confidence: 99%
“…Immunosuppression has been shown in multiple studies to be a negative independent prognostic factor for patients with MCC [24,28,29,39,40]. With regard to differential impact on clinical outcomes by etiology of immunosuppression in MCC, Cook et al [41] performed a retrospective analysis of 89 patients with non-metastatic MCC and found increased mortality risk for immunosuppressed patients with HIV/AIDS and organ transplant relative to patients with autoimmune disease (reference group). In an analysis of the NCDB, Yusuf et al found immune status to be an independent predictor of OS for patients with MCC by MVA, and found etiology of immunosuppression to be associated with OS with the lowest 3-year OS rates for immunosuppressed patients with solid organ transplants [24].…”
Section: Immune Statusmentioning
confidence: 99%
“…Between 2000-2013, there was a 95% increase in reported cases of MCC, as compared to a 15% increase in all solid tumors, and its incidence has quadrupled during the past 20 years [4]. Merkel cell polyomavirus (MCPyV) [5], ultraviolet (UV) exposure [6], and immuno-suppression [7] are known major risk factors. Although immune checkpoint inhibitors (ICIs) targeting programmed cell death protein one and its ligand (PD1/PD-L1) have become the standard of care for advanced MCC, resistance develops in the majority of treated patients [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%